Seed morphology and germination type of some species of dipterocarps - INDRIANI EKASARI; LUSI OKTAVIANI (Nusantara Bioscience, 2024)
Abstract. Ekasari I, Oktaviani L. 2024. Seed morphology and germination type of some species of dipterocarps. Nusantara Bioscience 16: 192-200. The dipterocarps seed conservation and effective seedling management of threatened plants required basic information on morphology and germination type to provide information on biological, ecological, and characteristics with taxonomic relevance. Seeds and seedlings characters can provide useful data in the delimitation and identification of species, including wings, sizes, shapes, germination type, and stages. The study aims to investigate the morphology and germination type of the seeds of some species of dipterocarps to contextualize and understand their ecological implications because the seed was the fundamental stage for the propagation and perpetuation of the species. This study was conducted for three months from seed collection, seed morphology measurement, seed sowing, and observation for germination type. The seeds from five species of dipterocarps (Shorea selanica, S. pinanga, S. stenoptera, Hopea gregaria, and Vatica pauciflora) were collected from the Forest Research and Development, Ministry of Forestry (FORDA), Dramaga, Bogor, Indonesia and they were brought to seed conservation laboratory in Bogor Botanical Gardens. The results showed six characters to describe each species seed (seed shape, the dimensions of longer wings, the dimensions of shorter wings, seed weight, seed length, and seed width). The S. pinanga showed the longest wings among others (152.25±9.93 mm), and H. gregaria showed the lightest weight (0.49±0.06 g). All species showed the same germination type (epigeal) with cotyledons that rise above ground. There were five stages of seed germination from radicle growth until cotyledon was removed or perfectly germinated for 90 days. The plantings and pathogens management were required to increase the Dipterocarpaceae seedlings' growth success. This finding was crucial for developing methods for seed conservation and tropical rainforest restoration.